La educación inclusiva en las instituciones educativas públicas de secundaria del distrito de Iquitos 2023 según estudiantes y docentes de inglés - Curto Garay, Juan Carlos (2024)
The main purpose of this research was to contrast the perceptions of secondary school students and English teachers about inclusive education in public schools in the district of Iquitos in the year 2023. This study was based on a comparative research, using field, contemporary transectional and univariate designs. The population of interest consisted of 1,788 students in the fifth grade of secondary school and 828 teachers. For the selection of the sample, a stratified sampling method with proportional allocation was used, resulting in the selection of 317 students and 56 teachers. Data collection was carried out using a validated and reliable questionnaire. The results revealed that the average (mean) of the variable “inclusive education”, in transformed scores from 0 to 100, of the study sample made up of students and teachers was 67.180 < 83.259 respectively. Similarly, the results by dimensions were: Inclusive culture (71.013 for students and 85.446 for teachers), Inclusive politics (57.971 for students and 75.387 for teachers), Inclusive practices (71.278 for students and 88.214 for teachers). In conclusion, there are statistically significant differences in the perception of inclusive education between the two study groups, as the p-value was 0.000, lower than α = 0.05.